A Brief Review of the Application of Neuroergonomics in Skilled Cognition During Expert Sports Performance - Tan, Sok Joo; Kerr, Graham; Sullivan, John P.; Peake, Jonathan M. (Frontiers in Human Neuroscience, 2019)
The elite sports environment provides a unique setting for studying human performance, where both cognitive and physical demands are high. Successful performance in sport is contingent upon key cognitive skills such as attention, perception, working memory and decision-making. The demands of competitive sport also increase loading on the central nervous system (CNS). Neuroimaging methods such as functional magnetic resonance imaging (fMRI), functional near infrared spectroscopy (fNIRS) and electroencephalography (EEG) offer the potential to investigate the cognitive demands of sport, neuroplasticity of athletes, and biofeedback training. However, practical and technical limitations of these methods have generally limited their use to laboratory-based studies of athletes during simulated sporting tasks. This review provides a brief overview of research that has applied neuroimaging technology to study various aspects of cognitive function during sports performance in athletes, alternative methods for measuring CNS loading (e.g., direct current potential), possible solutions and avenues of focus for future neuroergonomics research in sport.